Resistencia, periodismo y propaganda durante la Guerra de la Independencia: la Gazeta de la Provincia de Burgos (1811-1813) - Alberto Ausín Ciruelos (Cuadernos de Ilustración y Romanticismo)
The Gazeta de la Provincia de Burgos was the first newspaper to be published in the Spanish province of Burgos. It was founded during the Peninsular War in 1811 and its last issue was published on 7th May 1813. The gazette was the official propaganda tool used by the Junta Superior de la Provincia de Burgos (1809-1813). The weekly publication would always oppose the French army and the government of Joseph Bonaparte, known as king José I. Studying this newspaper provides a wealth of information on the ideological and public opinion warfare conducted in this province, which remained under enemy occupation for nearly six years.